Analysis of the Main Factors Causing Flexible Pavement Damage in Central Lombok Regency: (Case Study: Praya–Gerunung Highway and Sengkol Highway, Central Lombok Regency) - M Haris, M A Fahmi, S Hadi (Jurnal Handasah, 2025)
The problem in this study is how the level of damage, vehicle volume, vehicle factors and alternatives for repair. The purpose of this study was to determine the value of damage to the outer layer of the road, the volume of vehicles, the main factors causing the damage. Before conducting direct research into the field, the researcher carried out the preparatory stage. Research preparation consisted of preliminary survey literature research divided into road geometric surveys and field surveys. Data collection techniques used primary data consisting of traffic calculation data, road damage data and secondary data. Data analysis based on the method of clan clans. The results of the analysis show that the damage that occurred on the two roads included: Loose, Cracked, Holes, Patches, waves, and Grooves. The total area of damage to the Praya-Gerunung road is 576.16 m2 or (5.58%), based on the value of the percentage of damage, it is in the small category because the percentage of damage is 5% -20%, so the handling is a routine maintenance program. While the total area of damage to Jalan Raya Sengkol is 556.11 m2 or (3.9%), based on the percentage value of the damage, it is in the very small category because the percentage of damage is <5%. so that the handling is a routine and periodic maintenance program. The conclusion is based on the value of the damage, it is in the small category, while the number of 603 vehicles/hour is the peak hour of traffic volume, while the main factor causing road damage is the increase in traffic volume burden and alternative repairs. After identifying the damage, it is a routine and periodic government program